Predictors and pathway of maternal near miss: A case-control study in a tertiary care facility in Kolkata - Debayan Podder; Bobby Paul; Subhas C Biswas; Aparajita Dasgupta; Soumit Roy; Arkaprovo Pal (Wolters Kluwer Medknow Publications, 2022)
Background: Use of maternal near-miss (MNM) cases as an adjunct has been advocated to understand the processes of obstetric care because they share similar pathways as maternal deaths. Identifying the predictors and care pathway is crucial to improve the quality of care and end preventable maternal deaths. Materials and Methods: This case-control study was conducted at a tertiary care facility in Kolkata from May 2019 to March 2020. Women admitted with complications during pregnancy, childbirth, or within 42 days of postpartum, who met the World Health Organization (WHO) near-miss criteria, were identified as cases, and equivalent age-group matched controls were recruited. Sample size of 60 cases and 60 controls was estimated, assuming a power of 80%, level of significance 0.05, and case-control ratio of 1. After obtaining approval from the institutional ethics committee and informed written consent from the participants, data was collected through face-to-face interview and review of records. Statistical analysis including care pathway analysis (using three-delay model) was performed using Statistical Package for Social Sciences version 16. Results: Joint family type (adjusted odds ratio [AOR] [CI] = 5.06 [1.48, 7.28]), lack of antenatal checkups (AOR [CI] = 7.85 [1.47, 12.09]), previous history of cesarean section (AOR [CI] = 3.94 [1.09, 14.33]), first delay in seeking care (AOR [CI] = 13.84 [3.62, 32.83]), and preexisting medical disorders (AOR [CI] = 11.03 [4.62, 22.80]) were identified as significant predictors of MNM in the adjusted model. Significant difference in the proportion of first and second delays in the care pathway was observed between cases and controls. Conclusions: Identification of risk factors of MNM and pattern of delays in the care pathway will help improving quality of obstetric care.